Considerations for direct tanker loading on dairy farms - Biggers, Earl D. Jr. (Kansas State University, 2010)
The objective of this thesis is to examine the factors that a producer will want to consider when choosing the milk cooling and storage system for the dairy farm. The two systems studied are the traditional, on-farm, bulk tank system and the more recently developed, direct tanker loading system that uses glycol chilling plates. As a long-term investment, the choice of the refrigeration and storage system will have an impact on at least four dimensions of the dairy business. The capital cost of the milk cooling/storage system can range from 2% to 5% of the total capital investment in the farm. Milk cooling costs can also account for as much as 25% of the farm’s total electric costs. The system selected can also have an impact on the hauling charges and the hauling charges can account for as much as 10% of the dairy’s gross revenue. Lastly, the storage system selected may influence the range of markets available to the producer as not all processors accept milk from farms using direct tanker loading. Using an economic engineering approach, three hypothetical farm sizes were considered: milking 700, milking 1,400, and milking 2,100 cows. Capital and operating cost data were collected from three major dairy equipment manufacturers that service the Upper Midwest. Capital expenses for each size farm were priced for conventional bulk tanks and then also priced for glycol plate chiller systems that load directly into tanker trailers. The comparison of annualized costs of ownership for all three farm sizes shows only minor differences in the two systems. For the 700 cow farm, a direct tanker loading system saved 0.24% over the total capital investment; for the 1,400 cow farm, a direct tanker loading system saved 0.97%; and for the 2,100 cow farm, a direct tanker loading system saved 1.19%. Thus, differences in hauling charges, which will vary with each situation, become critical to the choice. Because the overall cost of the two systems are so close, one can expect that the peripheral and non-economic issues may be much more influential on each producer’s decision. Given the known differences in hauling charges, one can conclude that for the 700 cow farm, conventional tanks would be the preferred choice. For the 1,400 cow farm and the 2,100 cow farm, the determining factors come down to the differences in hauling charges and long-term goals for the farm business.
Keywords: Dairy Farm; Hauler; Milk Storage; Direct Tanker Loading; Cooling and Storage; Milk Hauling; Agriculture, General (0473); Economics, Agricultural (0503); Economics, Commerce - Business (0505)